Subthalamic nucleus deep brain stimulation changes velopharyngeal control in Parkinson’s disease - Hammer, Michael J. (2010)
PURPOSE: Adequate velopharyngeal control is essential for speech, but may be impaired in Parkinson’s disease (PD). Bilateral subthalamic nucleus deep brain stimulation (STN DBS) improves limb function in PD, but the effects on velopharyngeal control remain unknown. We tested whether STN DBS would change aerodynamic measures of velopharyngeal control, and whether these changes were correlated with limb function and stimulation settings. METHODS: Seventeen PD participants with bilateral STN DBS were tested within a morning session after a minimum of 12 h since their most recent dose of anti-PD medication. Testing occurred when STN DBS was on, and again 1 h after STN DBS was turned off, and included aerodynamic measures during syllable production, and standard neurological ratings of limb function. RESULTS: We found that PD participants exhibited changes with STN DBS, primarily consistent with increased intraoral pressure (n = 7) and increased velopharyngeal closure (n = 5). These changes were modestly correlated with measures of limb function, and were correlated with stimulation frequency. CONCLUSION: Our findings suggest that STN DBS may change velopharyngeal control during syllable production in PD, with greater benefit associated with low frequency stimulation. However, DBS demonstrates a more subtle influence on speech-related velopharyngeal control than limb motor control. This distinction and its underlying mechanisms are important to consider when assessing the impact of STN DBS on PD.